Sex-related differences in upper limb motor function in healthy subjects and multiple sclerosis patients: a multiparametric MRI study - Bonacchi, Raffaello; Valsasina, Paola; Pagani, Elisabetta; Meani, Alessandro; Preziosa, Paolo; Rocca, Maria A.; Filippi, Massimo (Journal of neurology, 2023)
Background We investigated sex-related differences in upper limb motor performance tested with the 9-Hole Peg Test (9HPT) in healthy controls (HC) and multiple sclerosis (MS) patients and their MRI substrates. Materials and methods We enrolled 94 HC and 133 MS patients, who underwent neurological examination, 9HPT and brain 3T MRI, with sequences for regional grey matter volume (GMV), white matter (WM) fractional anisotropy (FA) and resting state (RS) functional connectivity (FC) analysis. Associations between MRI variables and 9HPT performance were analyzed with general linear models. Results 9HPT performance was better in HC vs MS patients, and in female vs male HC. Regional GMV analysis showed: associations between better 9HPT performance and higher GMV in motor and cognitive cortical areas in HC, with stronger positive correlations in females vs males. In MS, worse 9HPT performance correlated with lower volume in motor and cognitive areas. Sex-related differences were minimal and mostly found in cerebellar areas. WM FA analysis disclosed neither associations with 9HPT performance in HC, nor sex-related differences in MS. RS FC analysis showed: in the sensorimotor network, stronger associations of RS FC with 9HPT performance in female vs male HC and no sex-related differences in MS; in the cerebellar network, no sex-related differences in HC but stronger negative correlation in left cerebellum in male vs female MS patients. Conclusions Sex influences 9HPT performance in HC, mainly through differences in volume and RS FC of motor and cognitive areas. Sex-related effects on motor performance become secondary but still present in MS.